MiR-362-5p, Which Is Regulated by Long Non-Coding RNA MBNL1-AS1, Promotes the Cell Proliferation and Tumor Growth of Bladder Cancer by Targeting QKI - Wei, Xiaosong; Wang, Beibei; Wang, Qi; Yang, Xiaoming; Yang, Yang; Fang, Zhiwei; Yi, Chengzhi; Shi, Lei; Fan, Xin; Tao, Jin; Guo, Yufeng; Song, Dongkui (Frontiers in Pharmacology, 2020)
In this study, we found miR-362-5p was upregulated in bladder cancer tissues and we predicted that QKI is potential a target of miR-362-5p and MBNL1-AS1 might be able to directly bind with miR-362-5p. We attempted to evaluate whether miR-362-5p could play its roles in bladder cancer through regulating QKI (quaking) and whether the expression and function of miR-362-5p could be mediated by lncRNA MBNL1-AS1. We performed the gain- and loss- function experiments to explore the association between miR-362-5p expression and bladder cancer proliferation. In vivo, the nude mice were injected with miR-362-5p knockdown SW780 cells to assess the effects of miR-362-5p on tumor growth. The results showed upregulation of miR-362-5p promoted cell proliferation of bladder cancer cells. MBNL1-AS1 and QKI could directly bind with miR-362-5p, and knockdown of MBNL1-AS1 or QKI could abrogate the regulatory effects of miR-362-5p on bladder cancer cell proliferation. Furthermore, downregulation of miR-362-5p inhibited bladder tumor growth and increased QKI expression. Our data unveiled that miR-362-5p may play an oncogenic role in bladder cancer through QKI and MBNL1-AS1 might function as a sponge to mediate the miR-362-5p expression and function.